2021
DOI: 10.3389/fpls.2020.594538
|View full text |Cite
|
Sign up to set email alerts
|

Flowering Phenology and the Influence of Seasonality in Flower Conspicuousness for Bees

Abstract: Flowering patterns are crucial to understand the dynamics of plant reproduction and resource availability for pollinators. Seasonal climate constrains flower and leaf phenology, where leaf and flower colors likely differ between seasons. Color is the main floral trait attracting pollinators; however, seasonal changes in the leaf-background coloration affect the perception of flower color contrasts by pollinators. For a seasonally dry woody cerrado community (Brazilian savanna) mainly pollinated by bees, we ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 62 publications
0
13
0
1
Order By: Relevance
“…In general, the clustering patterns of loci observed in the colour space of bees, flies, butterflies and birds were similar. Loci of flowers with chlorophylls occupied central position in all models and showed low chromatic contrast, which suggest that these flowers are difficult to perceive by the four groups of pollinators (Chittka et al, 1994;Endler and Mielke, 2005;Hannah et al, 2019), at least in environments where dominant background is green foliage (Endler, 2012;Bukovac et al, 2017;Martins et al, 2021). This fact may explain the low frequency of green flowers in local floras (Weevers, 1952;Dyer, 1996;Warren and Mackenzie, 2001).…”
Section: Discussionmentioning
confidence: 92%
“…In general, the clustering patterns of loci observed in the colour space of bees, flies, butterflies and birds were similar. Loci of flowers with chlorophylls occupied central position in all models and showed low chromatic contrast, which suggest that these flowers are difficult to perceive by the four groups of pollinators (Chittka et al, 1994;Endler and Mielke, 2005;Hannah et al, 2019), at least in environments where dominant background is green foliage (Endler, 2012;Bukovac et al, 2017;Martins et al, 2021). This fact may explain the low frequency of green flowers in local floras (Weevers, 1952;Dyer, 1996;Warren and Mackenzie, 2001).…”
Section: Discussionmentioning
confidence: 92%
“…In terms of importance, even for a small patch of vegetation, our study has reported the occurrence of several endemic cerrado species, as: Our cerrado sensu stricto species were pollinated mainly by bees, with more than a half of species presenting bee-pollinated flowers (Figure 4), as expected for Cerrado and other tropical vegetation systems (Gottsberger & Silberbauer-Gottsberger 2006, Monteiro et al 2021, Genini et al 2021) and stressing the relevance of preserving Cerrado remnants for this key ecosystem service. For the same community, Martins et al (2021) found that plant species with different flower colors presented distinct flowering peaks over the year but maintained color diversity over time. For example, while white flowers peaked in the transition between dry and wet season, matching with the community flowering peak, yellow flowers were distributed all year long, being an important resource during the dry season, when a reduced number of species is flowering (Martins et al 2021).…”
Section: Discussionmentioning
confidence: 95%
“…For the same community, Martins et al (2021) found that plant species with different flower colors presented distinct flowering peaks over the year but maintained color diversity over time. For example, while white flowers peaked in the transition between dry and wet season, matching with the community flowering peak, yellow flowers were distributed all year long, being an important resource during the dry season, when a reduced number of species is flowering (Martins et al 2021). The observed flowering pattern provide functional diversity over time, contributing to the presence of different groups of pollinators such as bees, small insects, flies and hummingbirds, and nocturnal pollinators such as Sphingidae moths and bats (Gottsberger & Silberbauer-Gottsberger 2006, Amorim et al 2009.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A posterior study showed that, instead, the corolla color of spring flowers in temperate deciduous forests are lighter than non-spring flowers, but not necessarily white (Hensel & Sargent 2012). In the Brazilian Savanna, yellow flowers were abundant year around, but white flowers peaked in the dry season, and pink flowers in the wet season (Martins et al 2021). Indeed, in Itatiaia National Park (Brazil), community level fitness increased with synchronous flowering and color similarities, using visual systems of bees, flies and birds (Bergamo et al 2020).…”
Section: Flowering Season and Habitatmentioning
confidence: 99%